INDONESIA’S FEMINIST FOREIGN POLICY IN COMBATING TRAFFICKING IN PERSONS (TIP) ESPECIALLY WOMEN AND CHILDREN 2020-2023 - Naeli Fitria (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study critically examines Indonesia’s feminist foreign policy approach in addressing trafficking in persons (TIP), particularly affecting women and children, during the leadership of Foreign Minister Retno Marsudi (2020–2023). Drawing on feminist international relations theory and foreign policy analysis (FPA), the paper explores how Indonesia operationalized gender-sensitive diplomacy through both internal and external mechanisms. Internally, key drivers included Marsudi’s leadership, bureaucratic reforms, civil society engagement, and national legislation aligned with human rights commitments. These factors enabled the mainstreaming of feminist values such as intersectionality, trauma-informed victim support, and survivor-centered approaches into foreign policy practices. Externally, Indonesia navigated the normative constraints of ASEAN’s non-interference principle while promoting the ASEAN Convention Against Trafficking in Persons (ACTIP) through silent diplomacy and norm entrepreneurship. The study highlights Indonesia’s strategic use of soft law, coalition-building, and cross-sectoral partnerships to advance gender-justice frameworks within regional and global diplomatic arenas. It further demonstrates how feminist diplomacy in a Global South context may deviate from overt ideological declarations, favoring pragmatic and culturally resonant approaches. Through qualitative document analysis and case-based inquiry, this paper reveals the potential of feminist foreign policy to influence international anti-trafficking norms without undermining regional cohesion. Indonesia’s experience offers an alternative model of feminist diplomacy characterized by quiet persistence, inclusive engagement, and context-specific implementation. The findings contribute to broader debates on how non-Western states can localize and institutionalize feminist foreign policy principles within constrained geopolitical settings.